Religious Arguments in the Public Sphere: A View from Israel - Sapir, Gidon (Journal of law, religion and state, 2012)
It is commonly believed that, from a liberal point of view, there is something problematic in government action rooted in religious considerations. We begin by showing exactly what kind of religious considerations might thought to be ruled out as a basis for such action. We then discuss at length the approach expressed by the Supreme Court of Israel, according to which legislation and other government actions based on religious considerations are problematic because they violate the right to freedom from religion of non-religious citizens. We reject the court’s interpretation of this right and conclude that the court has failed to explain why government action based on religious considerations is illegitimate.